Haematophysiological Effects of Carica Papaya (Pawpaw) Leaves Extracts on Albino Wistar Rats Previously Treated with Phenyldrazine - Eze, I.R. , Achukwu U.P. , Omorodion, N.T. * , Belonwu, N.J.K. (Sokoto Journal of Medical Laboratory Science)
Carica papaya (pawpaw) plant has been used for several years for its medicinal values such as anti- sickling properties, coagulation, anti-inflammatory and anti-malarial effects. This study was performed using ethanolic extract of the leaves to determine its ability to reverse haemolytic anaemia. Twenty-four albino Wistar rats weighing between 115-200g were used. The rats were grouped into four (Control group and Group I, II, and III). The rats were treated with 10mg/kg weight of phenylhydrazine. Control was given no treatment. Group l served as positive control and were administered HB B 12 (1ml/150kg body weight). The experimental groups (ll and lll) were administered 200 and 100mg/kg body weight orally respectively for 28 consecutive days. At the end of the 28 days, samples from all groups were re- analyzed for all haematological parameters. Results are expressed as mean ± standard deviations for the all groups and analyzed statistically, the result showed significant increase (p<0.05) in the packed cell volume, haemoglobin concentration, platelet count and mean cell haemoglobin concentrations and no significant increase (p>0.05) in the mean cell haemoglobin, mean cell volume, reticulocyte count, total white cell count, red blood cell count, basophil, eosinophil, monocyte, lymphocytes and neutrophils amongst group l, ll, lll. There was a statistically significant increase (p<0.05) in pack cell volume of the three groups l (0.398±0.008), group ll (0.382±0.016), group lll (0.365±0.014) respectively. Heamoglobin concentration of group l increased significantly to (14.980±2.620) while that of the experimental groups (group l and ll) did not increase significantly increased order to reverse to pre-induction. Recticulocytosis significantly decreased (p<0.05) in the three groups (group l, ll, ll), whereas platelet count was significantly increased only in the experimental groups (group ll, lll) with values of (1248±71.052) and (982.833±177.42). Hymenolepsis diminuta (rat tapeworms) were expelled from the rat in all the groups. The extract did not serve sufficient to increase the overall blood loss as efficiently as HB 12. Overall, the HB 12 had better haematic effect than both concentration of the Carica papaya. HB 12 was able to restore haemoglobin and pack cell volume.